Pengaruh Religiusitas dan Insentif Keuangan terhadap Intensi Melakukan Whistleblowing pada Faith-Based Organization - Andrey Hasiholan Pulungan (Ekonomi dan Bisnis, 2018)
Whistleblowing, nowadays, is a common practice many organizations to detect fraud. This research aims to analyze the extent of the effect of financial incentives on employees’ intentions in faith-based organizations (FBO) to do whistleblowing. Individuals who works in FBO have different characteristics from individuals who work in profit-oriented companies. One of the characteristic uniqueness of employees who work in FBO is their motivation to work is more driven by religious values rather than financial incentives. Using the between-group subjects design, the results shows that religious and financial incentives affect the intentions of FBO employees to report fraud.